Analysis of Effectiveness and Efficiency in MSME Management for Increasing Income in Mendalo Darat Village, Muaro Jambi - Rafidah, Rafidah; M. Nazori; Rosmanidar, Elyanti; Mutia, Agustina; Usdeldi, Usdeldi; Anita, Efni; Fusfita, Nurlia; Rahma, Sri; M. Subhan; Nofriza, Eri; Alawiyah, Rabiyatul (PT Inovasi Pratama Internasional, 2024)
The problem in this study is the decline in the income level of MSME actors during the Covid-19 pandemic, one of the reasons for this is the lack of effectiveness and efficiency of financial management in their businesses, business actors feel they do not understand how to make policies in managing their business finances. The purpose of this study is to determine the effectiveness and efficiency of MSME Mendalo Darat in increasing income and to find out what obstacles are experienced by MSME Mendalo Darat actors in efforts to increase income. The type of method in this study is field/qualitative research. The income of MSME Mendalo Darat has decreased in the Covid-19 era so that e-commerce has a positive impact on the income of MSME Mendalo Darat.